The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1097/gox.0000000000004683
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism Risk Assessment Models in Plastic Surgery: A Systematic Review and Meta-Analysis

Abstract: Background: Postoperative venous thromboembolism (VTE) is the most common complication of plastic surgery procedures. Diverse risk assessment models (RAMs) exist to stratify patients by VTE risk, but due to a lack of high-quality evidence and heterogeneity in RAM data, there is no recommendation regarding RAM that can be used for plastic surgery patients. This study compares the reliability and outcomes of Caprini and American Society of Anesthesiologists (ASA) physical status classification RAMs u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The results showed that patients with higher Caprini scores had a greater risk of postoperative VTE. In addition, in their systematic review, Mrad et al 35 reported that the Caprini RAM is more predictive of postoperative VTE incidents in high-risk plastic surgery patients than is the American Society of Anesthesiologists grading system. These findings highlight the advantages of the Caprini RAM in effectively identifying patients at risk of VTE, thereby allowing for timely interventions and preventive measures to mitigate this serious complication.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that patients with higher Caprini scores had a greater risk of postoperative VTE. In addition, in their systematic review, Mrad et al 35 reported that the Caprini RAM is more predictive of postoperative VTE incidents in high-risk plastic surgery patients than is the American Society of Anesthesiologists grading system. These findings highlight the advantages of the Caprini RAM in effectively identifying patients at risk of VTE, thereby allowing for timely interventions and preventive measures to mitigate this serious complication.…”
Section: Discussionmentioning
confidence: 99%